Carbohydrate metabolism in floral structures of Lilium pumilum in different development stages - Mirelle Nayana de Sousa Santos; Ana Maria Mapeli; Márcia Martins Tolentino (Ciência Rural, 2016)
ABSTRACT: Lilium pumilum is a species that stands out in floriculture for presenting orange inflorescences that attract the consumer. This study thus aimed at characterizing the carbohydrate metabolism of floral structures of L. pumilum in different development stages. For this purpose, carbohydrate levels (total soluble sugars, reducing sugars, non-reducing sugars, and starch), at different floral stages (E0 - bud with no color; E1 - bud at early coloring; E2 - orange bud; E3 - open flower; E4 - senescent flower) were quantified after extraction with ethanol. Lilium pumilum flowers showed high energy potential during floral opening and senescence; total soluble sugars were the main carbohydrates present in the species, reducing with the floral development, and the same occurred with the non-reducing sugar and starch contents. The reducing-sugar content increased with the floral stages. Therefore, this species presents great mobilization of compounds, which are utilized in the production of energy that is employed in floral opening.